Bioestímulo de solo de milhocultura com resíduo de malte de cevada oriundo do setor cervejeiro artesanal - Medeiros, Hércules Gonçalves de Almeida (2023)
Corn is an important cereal produced and consumed in various parts of the world, in which Brazilian production occupies one of the first places in the ranking. In the Northeast region of Brazil, the cultivar plays an important role in food security and guarantees income for the population. Agroindustry is a growing sector in Paraíba, with emphasis on the brewing industry, and the sector generates waste in high quantities. Barley malt residue is underutilized and still little explored, due to technological difficulties and lack of research, mainly for agriculture. Therefore, the objective of this study is to elucidate the agricultural potential of barley residue as a possible stimulus on the soil microbiota, which is closely linked to plant development, favoring fertility in production. For this, corn (Zea mays) was cultivated in pots filled with earth or sand, testing substrates with different proportions of barley malt residue with the following treatments: T1, T2, T3, T4, T5, respectively: treatment control; 2.5% barley malt residue, 5%, 10% and Sand + fertilizer NPK.. Substrate samples at the beginning and on the 50th day of cultivation were collected for microbiological analysis. The analyzed variables were submitted to statistical analyses. In the results it was observed that the treatments T3 and T4 with addition of 5% and 10% of RMC influenced in the greater development of the corn plants, related to the height, mass of the aerial part and of the roots, but the influence in the microbiota of the soil was little expressive, considering the analyzed periods. It was concluded that the addition of barley malt residue did little to promote soil microorganisms that promote plant growth and promoted greater development of corn plants.